Physicochemical properties of Indica rice starch modified by mechanical activation and octenyl succinic anhydride. (6th April 2017) - Zhang, Zhengmao; Zhao, Siming; Xiong, Shanbai
Abstract : Three types of modified Indica rice starch were obtained by combining mechanical activation (MA) with octenyl succinic anhydride (OSA) esterification. The samples were mechanically activated Indica rice starch (MA‐IRS), mechanically activated Indica rice starch esterified by OSA (OSA‐MA‐IRS) and Indica rice starch that was esterified by OSA and mechanically activated (MA‐OSA‐IRS). The physicochemical properties of the three types of modified Indica rice starch were studied. The results indicate that the particle shape of OSA‐MA‐IRS was the most irregular among the three types of modified Indica rice starch, and the changes in morphology of MA‐OSA‐IRS were similar to those in mechanically activated Indica rice starch (MA‐IRS), but the granules of MS‐OSA‐IRS were smaller than the granules of MA‐IRS after an identical mechanical activation time. The results of X‐ray diffraction showed that a new crystalline structure formed during preparation of OSA‐MA‐IRS, and the crystal structure of OSA‐IRS was more easily destroyed by mechanical force than that of IRS. Therefore, for the same mechanical activation time, the transparency and reducing power for each sample were ranked in the following order: MA‐OSA‐IRS, MA‐IRS, and OSA‐MA‐IRS. However, the blue value from iodine staining and apparent viscosity showed the reverse trend. The emulsifying activity index decreased in the following order: OSA‐MA‐IRS, MA‐OSA‐IRS, and MA‐IRS.